The Effect of Baseline Component Correlation on the Design of GNSS Network Configuration for Sermo Reservoir Deformation Monitoring - Subagyo Pramumijoyo; Nurrohmat Widjajanti; Yulaikhah Yulaikhah (Indonesian Journal of Geography, 2019)
The condition of the geological structure in the surrounding Sermo reservoir shows that there is a fault crossing the reservoir. Deformation monitoring of that fault has been carried out by conducting GNSS campaigns at 15 monitoring stations simultaneously. However, those campaigns were not well designed. With such a design, it took many instruments and spent much money. For the next GNSS campaign, it should be designed so that the optimal network configuration is obtained and the cost can be reduced. In the design of deformation monitoring network, sensitivity criteria become very important for detecting the deformations. In GNSS relative positioning, the baseline components are correlated, but this correlation is often ignored. This research examined the effect of baseline component correlations on the design results of the GNSS configuration of the Sermo Fault network based on sensitivity criterion. In this case, the western side of the fault was taken as a reference, while the other side as an object moving relatively against the western side. This study found that the baseline component correlation affects the results of GNSS network configuration. Considering the correlation could result a sensitive network configuration with a fewer baseline; therefore, the cost and time of field surveys can be reduced. It can be said that the baseline component correlation needs to be taken into account in the configuration design of deformation monitoring network.